Our first Civil War : [large type] patriots and loyalists in the American Revolution - Brands, H. W. (Random House Large Print, 2021)
What causes people to forsake their country and take arms against it? George Washington in the 1770s stood at the apex of Virginia society. Benjamin Franklin was more successful still, having risen from humble origins to world fame. John Adams revered the law. Yet all three men became rebels against the British Empire that fostered their success. Others in the same circle of family and friends chose differently-- and soon heard themselves denounced as traitors for not having betrayed the country where they grew up. Brands reminds us that before America could win its revolution against Britain, the Patriots had to win a bitter civil war against family, neighbors, and friends. -- adapted from jacket.